Processing and microstructural characterization of functionally gradient Al A359/SiCp composite - Rodriguez-Castro, R; Kelestemur, MH (Kluwer Academic Publ, 2002)
A centrifugal casting method is presented in this paper for processing Al/SiCp Functionally Gradient Material (FGM), along with the corresponding microstructural characterization. Results are presented and discussed on SiC particles distribution, particles-solidification front interactions, matrix micro-structure, and porosity distribution in the castings as a function of the centrifugal forces applied. Three different casting rotational speeds (700, 1000 and 1300 rpm) were utilized while keeping all other casting conditions constant. For the highest speed applied, a variation of graded composition in the range of 20 to 44 vol% of SiC was obtained. Moreover, such progressive concentration of particles was observed to be very homogeneous due to engulfment of particles (promoted by the high relative velocity between the solidification front and particles) and also as a consequence of elevated cooling rates developed in this case. Additional results showed that the matrix micro-structure is modified according to the SiC reinforcement content and cooling rates, which both depend on the centrifugal forces applied. (C) 2002 Kluwer Academic Publishers.
Keywords: Graded Material; Solidification; Behavior